Taiwan-China Issue in the South China Sea - Toshbekov Bobur (Cita konsultindo, 2023)
This article examines the long-standing territorial dispute between China and Taiwan in the South China Sea, which has caused tension and conflict in the region for several decades. The article analyzes the role of negotiation and conflict in resolving this issue, particularly in the context of China's military buildup and the involvement of other regional nations. The findings of this research suggest that effective negotiation and conflict resolution strategies are essential for resolving the Taiwan-China problem in the South China Sea and ensuring peace and stability in the region